IN VITRO EFFECT OF PHARMACEUTICAL EFFLUENT ON HAEMATOLOGY AND BIOCHEMICAL RESPONSES IN AFRICAN CATFISH (CLARIAS GARIEPINUS) - Nafiu Abdullahi, Shafiu; Zakariyya, M.; Hassan, Z. Y.; Ahmad, M. K. (FUDMA JOURNAL OF SCIENCES, 2021)
Pharmaceutical effluents collected from Bompai industrial area, Kano State were assessed for their physiochemical parameters, heavy metals and effect on haematology and biochemical changes in Clarias gariepinus. Laboratory analyses were performed using standard methods in a Completely Randomized Design (CRD). Five test solutions of the effluents (0, 25, 50, 75, and 100% v/v) were prepared for LC50 96hr acute toxicity test. The LC50 for 96hr was 48.7% concentration of effluents by volume. Experimental fish were exposed to sublethal concentrations of 0.00% 2.43% (5/100 LC50), 12.17% (25/100 LC50), 24.35% (50/100 LC50) and 36.52% (75/100 LC50) for 28days.  Physicochemical parameters recorded were higher than WHO recommended Standard with the exception of water temperature. Heavy metals concentrations decreased in the order of Cr > Cu > Pd > Cd. Red blood Cells count, haemoglobin concentrations, packed cell volume, lymphocytes and monocytes of the experimental fish decline significantly (p<0.05) when exposed with 2.43, 12.17, 24.35, 36.52% effluents  compared to the control. White blood cell count, mean corpuscular haemoglobin, mean corpuscular volume, mean corpuscular haemoglobin concentrations, neutrophils and eosinophils were significantly higher (P<0.05) than the control. However, a significant increase (P<0.05) in the activities of serum aspartate aminotransferase (AST), Alkaline Phosphatase (ALP) and alanine aminotransferase (ALT) were recorded as the exposure period continued when compared with control. It is concluded that the effluents induces haematological and biochemical alterations. It is therefore recommended that regulatory bodies should adopt holistic approach on the aquatic pollution abatement, bearing in mind the negative impact to non-target organisms.